When parenting fails: alexithymia and attachment states of mind in mothers of female patients with eating disorders - Pace, Cecilia Serena; Cavanna, Donatella; Guiducci, Valentina; Bizzi, Fabiola (Frontiers in Psychology, 2015)
Introduction. In recent years alexithymia and attachment theory have been recognized as two parallel research lines trying to improve the information on the development and maintenance of eating disorders (EDs). However no research has analyzed these constructs among patients’ families. In this study we compared alexithymia and attachment in mothers of patients with EDs and a control group. Further, we hypothesized that mothers of daughters with EDs with insecure and unresolved states of mind will reported high levels of alexithymia. Lastly, we explored the daughters’ evaluations of maternal alexithymia. Method. 45 mothers of ED women and 48 mothers of healthy controls (N= 93) matched for age and socio-demographic variables were administered by the Toronto Alexithymia Scale-20 (TAS-20) S), while two sub-groups of “ED” mothers (n = 20) and “non-ED” ones (n = 22) were assessed by the Adult Attachment Interview (AAI). Moreover, the Observer Alexithymia Scale (OAS) was administered to the daughters for evaluating maternal alexithymia. Results. Regarding alexithymia, no differences were found between ED and non-ED mothers according to the TAS-20, while ED mothers showed more unresolved AAI classifications than non-ED mothers. No correlations were found between the TAS-20 and the AAI. Lastly, ED mothers were evaluated more alexithymic by their daughters with the OAS than those in the control group, and their alexithymic traits were significantly correlated with dismissing states of mind (idealization and lack of memory) in the AAIs. Discussion. Our results highlighted an interesting discrepancy among mothers with ED daughters between the low level of alexithymia provided by their self-reports and the high level of alexithymia observed by their daughters, although the OAS showed severe methodological limitations. Maternal attachment states of mind characterized by the lack of resolution of past losses could be connected to a confusing and incoherent quality of parenting.